Predictors for Good Therapeutic Outcome and Drop‐out in Technology Assisted Guided Self‐Help in the Treatment of Bulimia Nervosa and Bulimia like Phenotype. (1st December 2014) - Wagner, Gudrun; Penelo, Eva; Nobis, Gerald; Mayrhofer, Anna; Wanner, Christian; Schau, Johanna; Spitzer, Marion; Gwinner, Paulina; Trofaier, Marie‐Louise; Imgart, Hartmut; Fernandez‐Aranda, Fernando; Karwautz, Andreas
Abstract Objective Technology assisted guided self‐help has been proven to be effective in the treatment of bulimia nervosa (BN). The aim of this study was to determine predictors of good long‐term outcome as well as drop‐out, in order to identify patients for whom these interventions are most suitable. Methods One hundred and fifty six patients with BN were assigned to either 7 months internet‐based guided self‐help (INT‐GSH) or to conventional guided bibliotherapy (BIB‐GSH), both guided by e‐mail support. Evaluations were taken at baseline, after 4, 7, and 18 months. As potential predictors, psychiatric comorbidity, personality features, and eating disorder psychopathology were considered. Results Higher motivation, lower frequency of binge eating, and lower body dissatisfaction at baseline predicted good outcome after the end of treatment. Lower frequency of binge eating predicted good outcome at long‐term follow‐up. Factors prediciting drop‐out were higher depression and lower self‐directedness at baseline. Conclusion Technology assisted self‐help can be recommended for patients with a high motivation to change, lower binge‐eating frequency and lower depression scores. Copyright © 2014 John Wiley & Sons, Ltd and Eating Disorders Association.